A mental skills package for Special Olympics athletes: A preliminary study - Gregg, M.; Hrycaiko, D.; Martin, G. L.; Mactavish, J. (Adapted Physical Activity Quarterly, 2004)
The purpose in this study was to replicate and extend the mental skills training (MST) package of Wanlin, Hrycaiko, Martin, and Mahon (1997) to Special Olympics track and field athletes with intellectual disabilities. Three participants ranged in age from 21 to 23 years. A multiple baseline design across individuals was used to assess the effects of the intervention on off-task behaviors and athletic performance (i.e., work output and competition results). The results were clearly beneficial for two participants, decreasing the frequency and duraton of off-task behaviors and increasing the percentage of laps completed for the third participant. A social validity assessment provided further support for the effectiveness of the intervention.